Hierarchy of Effect: Dampak Persepsi terhadap Konten Pemasaran dan Kualitas Produk dalam Keputusan Pembelian Produk Mie Lidi Nyonyah Cetar - Setyowati, Ratna Faridah; Sriyanto, Agus; Agung, Ign. Sigit Budi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The development of information and marketing technology in an effort to increase purchasing interest in Micro, Small and Medium Enterprises (MSMEs) products is important to implement. This research aims to confirm the effectiveness of the synergy between content marketing strategies and Mie Lidi Nyonyah Cetar product quality by adding purchase interest as a mediating variable within the framework of the Hierarchy of Effect theory. This model describes the stages that consumers go through from initial awareness to purchase action, and can provide valuable insight into the effectiveness of Mie Lidi Nyonyah Cetar's marketing strategy. The research used descriptive methods and quantitative analysis through a questionnaire survey of 140 active digital audience respondents on Instagram and WhatsApp. Data analysis in this research used SEM (Structural Equation Model) using the LISREL 8.8 program. The research results show that content marketing and product quality have a direct negative and insignificant influence on purchasing decisions. Purchase interest has a positive and significant effect on purchasing decisions. Content marketing and product quality have a positive and significant effect on purchasing interest. Content marketing and product quality have a positive and significant effect on purchasing decisions through purchase interest. Based on these results, it can be concluded that the content marketing and product quality of Mie Lidi Nyonyah Cetar have been able to prove the Hierarchy of Effect Theory with purchase interest as the key factor that connects consumer knowledge about the product (cognitive) with purchasing actions (conative).